Investigating plant growth dynamics of selected southern highbush blueberry (V. corymbosum L. interspecific hybrids) cultivars under South African growing conditions - Steyn, Juan (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.